Numerical and Experimental Verification of Spherically Layered Ice Model for Analysis on Hail Impacting Aviation Structures - Gang Luo; Fengqi Zhang; Wanting Cao; Haiyang Zhang; Lulu Liu; Wei Chen (International Journal of Aerospace Engineering)
Aviation structures are required to be resistant to impact damage from hail. Therefore, aiming to gain a better understanding of such impacts, the formation mechanisms, spherically layered structures, and layer-density distributions of real hail were investigated. Based on analysis of the influence of different constitutive model parameters on the impact load on a metal target plate, a layered finite-element hail model was established, and this and several equivalent hail models were simulated and compared in terms of the dynamic responses during impact with a Ti6Al4V alloy plate target. The results showed that the characteristic values of the contact forces and impact displacements of spherically layered hail were lower than those for equivalent hailstones with the same mass or diameter. The spherically layered modeling of hail could provide a method for fine analysis of the phenomenology of hailstone impacts.